Actuator fault tolerant control via active fault diagnosis for a remotely operated vehicle. Issue 6 (2022) - Baldini, Alessandro; Felicetti, Riccardo; Freddi, Alessandro; Longhi, Sauro; Monteriù, Andrea
Abstract: Unmanned underwater vehicles operate in unstructured and harsh environments, and fault diagnosis together with fault tolerant control play a crucial role to prevent the mission from failing. When a fault occurs in presence of unknown disturbances, such as unknown marine current or hitting an obstacle, actuator fault diagnosis becomes more challenging, because the unexpected forces that arise from disturbances may be mistaken for actuator faults. In this paper, we propose an active fault diagnosis method to discern between an actuator fault and any other disturbance: the former is modelled as a multiplicative input fault, and the latter is an unknown, additive, time varying force. Once the actuator faults have been isolated and identified, their estimations are fed to the control allocation algorithm to perform fault tolerant control allocation. Simulation results are performed with a realistic non-linear model to show the effectiveness of the proposed strategy.